Biochemistry of storage lesions of red cell and platelet concentrates: A continuous fight implying oxidative/nitrosative/phosphorylative stress and signaling. Issue 3 (June 2015) - Rinalducci, Sara; Zolla, Lello
Abstract: The mechanisms responsible for the reduced lifespan of transfused red blood cells (RBCs) and platelets (PLTs) are still under investigation, however one explanation refers to the detrimental biochemical changes occurring during ex vivo storage of these blood products. A myriad of historical and more recent studies has contributed to advance our understanding of storage lesion. Without any doubts, proteomics had great impact on transfusion medicine by profiling the storage-dependent changes in the total detectable protein pool of both RBCs and PLTs. This review article focuses on the role of oxidative/nitrosative stress in developing RBC and PLT storage lesions, with a special glance at its biochemistry and cross-talk with phosphorylative signal transduction. In this sense, we enlighten the potential contribution of new branches of proteomics in identifying novel points of intervention for the improvement of blood product quality.